Hepatoprotective effects of sesamol loaded solid lipid nanoparticles in carbon tetrachloride induced sub‐chronic hepatotoxicity in rats. Issue 5 (20th November 2014) - Singh, Neha; Khullar, Neeraj; Kakkar, Vandita; Kaur, Indu Pal
ABSTRACT: Sesamol is a phenolic component of sesame seed oil, which has been established as an antioxidant and also possesses potential for hepatoprotection. However, its protective role in carbon tetrachloride (CCl4 ) induced sub‐chronic hepatotoxicity has not been studied. Limited oral bioavailability (BA) and rapid elimination (as conjugates) in rats is reported for sesamol. Considering its significant antioxidant potential and compromised BA, we packaged sesamol into solid lipid nanoparticles (S‐SLNs) to enhance its hepatoprotective bioactivity. S‐SLNs prepared by microemulsification method were nearly spherical in shape with an average particle size of 120.30 nm and their oral administration at 8 mg/kg body weight (BW) showed significantly ( p < 0.001) better hepatoprotection than free sesamol (FS) and a well established hepatoprotective antioxidant silymarin [SILY (25 mg/kg BW); p < 0.05) in CCl4 induced sub‐chronic liver injury in rats. Evaluations were done in terms of histological changes in the liver tissue, liver injury markers (serum alanine aminotransferase, serum aspartate aminotransferase, and serum lactate dehydrogenase); oxidative stress markers (lipid peroxidation, superoxide dismutase, and reduced glutathione) and proinflammatory response marker (tumor necrosis factor‐alpha). © 2014 Wiley Periodicals, Inc. Environ Toxicol 31: 520–532, 2016.